THE LEGACIES OF APARTHEID: NATIONALISM, RACISM, AND XENOPHOBIA IN SOUTH AFRICA - Chigozie Felicity Obasi; Arba’iyah Mohd Noor; Nur Dayana Mohamed Ariffin (SEJARAH: Journal of the Department of History, 2025)
This study aims to investigate the historical and political roots of xenophobia in post- apartheid South Africa, arguing that it is not an isolated phenomenon but a "Legacies" of apartheid's systemic racism and an incomplete democratization process. Since 1994, South Africa has experienced persistent and violent xenophobia, predominantly targeting Black African migrants. A central paradox is the racial selectivity of this hostility, which largely spares White and non-African foreigners. This raises a critical question: is this xenophobia a new crisis of governance and economics, or a continuation of apartheid's institutionalised exclusion? The research challenges ahistorical explanations of xenophobia that focus solely on contemporary economic pressures. By tracing its continuities with apartheid, the study provides a deeper structural and cultural analysis, with significant implications for policy, transitional justice, and South Africa's role in pan-African solidarity. A qualitative, multi- method approach is employed, integrating: a historical analysis of apartheid-era laws and nationalism; critical discourse analysis of media and state rhetoric; and semi-structured interviews with 15 participants, including migrants from Zimbabwe, Mozambique, and Nigeria, and South African activists and political actors. The analysis reveals that xenophobia is deeply rooted in apartheid's racial hierarchies and exclusionary logics, which have been repackaged in the democratic era. Key findings include the persistent racial selectivity of attacks (Afrophobia), the scapegoating of migrants for the failures of full democratisation, and the use of xenophobia as a political tool by populist movements. The article concludes that xenophobia is a structural legacy of apartheid, sustained by unresolved historical trauma and economic inequality. Effective responses must therefore go beyond law enforcement to include substantive socioeconomic redress, civic education against xenophobia, strengthened regional cooperation, and a renewed transitional justice process that addresses economic reparations.